Validation of the psychometric properties of cognitive fusion questionnaire. A study of the factorial validity and factorial invariance of the measure among osteoarticular disease, diabetes mellitus, obesity, depressive disorder, and general populations - Costa, Joana (2017)
Background The cognitive fusion questionnaire (CFQ) is a self‐report questionnaire that assesses the extent to which individuals are psychologically entangled with, and dominated by the form–content of their thoughts. The aim of this study was to replicate the factor structure of CFQ in osteoarticular disease, diabetes mellitus, obesity, depressive disorder, and normative population. It further examined the factorial invariance of the CFQ across these 5 groups. Method Data from 299 participants (N General Population = 67, N Osteoarticular Disease = 73, N Diabetes Mellitus = 47, N Depressive Disorder = 45, and N Obesity = 60) were subjected to confirmatory factorial analysis (CFA) to replicate the structural model of CFQ dimensionality. Results CFA supported a 1‐factor structure with good internal consistency and construct related validity. The 1‐factor solution was also supported by a second independent data set, which showed a configural, strict measurement, and structural invariance of the 1‐factor solution proposed. Multigroup CFA showed the configural invariance, strict measurement invariance, and structural invariance of CFQ across the 5 groups under study. Conclusions The unidimensional model has both similar meanings and the same structure, but the measurement model across the groups was not the same. The study provides the first approach to CFQ to Portuguese population, as a reliable tool of general cognitive fusion. Furthermore, results indicated that CFQ has a coherent structure across multiple samples and clinical utility, as it discriminate individuals with psychological distress from those who do not.